Effects of Benzoquinones on Radicles of Orobanche and Phelipanche Species - Mónica Fernández-Aparicio; Marco Masi; Alessio Cimmino; Antonio Evidente (Plants, 2021)
The holoparasitic broomrape weeds (Orobanche and Phelipanche species) cause severe yield losses throughout North Africa, the Middle East, and Southern and Eastern Europe. These parasitic weeds form an haustorium at the tip of their radicles to infect the crop upon detection of the host-derived haustorium-inducing factors. Until now, the haustorial induction in the broomrapes remains less studied than in other parasitic plant species. Known haustorium-inducing factors active in hemiparasites, such as Striga and Triphysaria species, were reported to be inefficient for the induction of haustoria in broomrape radicles. In this work, the haustorium-inducing activity of p-benzoquinone and 2,6-dimethoxy-p-benzoquinone (BQ and DMBQ) on radicles of three different broomrapes, namely Orobanche cumana, Orobanche minor and Phelipanche ramosa, is reported. Additional allelopathic effects of benzoquinones on radicle growth and radicle necrosis were studied. The results of this work suggest that benzoquinones play a role in the induction of haustorium in broomrapes. Although dependent on the broomrape species assayed and the concentration of quinones used in the test, the activity of BQ appeared to be stronger than that of DMBQ. The redox property represented by p-benzoquinone, which operates in several physiological processes of plants, insects and animals, is invoked to explain this different activity. This work confirms the usefulness of benzoquinones as haustorium-inducing factors for holoparasitic plant research. The findings of this work could facilitate future studies in the infection process, such as host-plant recognition and haustorial formation.